PHYTOCHEMICAL SCREENING AND ANTIOXIDANT ACTIVITY OF ETHANOL EXTRACT OF GALOBA DURIAN FRUIT PEEL (Ammomum spp.) - Salamena, Fuadiska; Manurung, Brian Saputra; Mose, Windi; Patty, Kristi Lenci; Nusaly, Windy Natalia; Putri Usman, Dwi Anggara (Meditory : The Journal of Medical Laboratory, 2025)
Background: Amomum spp. (red variant), An endemic plant widely found in Maluku, including Hatu Village, Ambon, is valued for its medicinal and economic roles.Objective: This study aimed to evaluate the phytochemical content and antioxidant activity of Ammomum peel extract using the DPPH assay.Methods: The fruit peel of Ammomum spp. (red variant) was extracted by maceration using ethanol as solvent and concentrated by evaporation at room temperature. The antioxidant activity was quantitatively and qualitatively assayed using the DPPH assay method and by observing the color change in the extract. Percent inhibition data were analyzed using linear regression.Results: The analytical findings confirmed the presence of flavonoids, saponins, tannins, steroids, and phenolics as secondary metabolite content in the galoba fruit peel extract. The free radical scavenging activity exhibited a strong value of 59.04 µg/mL. Therefore, this study suggests using the red variant of Ammomum spp. fruit peel extract in the treatment of free radical-induced disorders.Conclusions: Our study revealed that the peel extract of red Galoba durian contained secondary metabolites and strong antioxidant activity.